A novel fault detection and diagnostic petri net methodology for dynamic systems - Badmus, Taofeeq Alabi (2025)
Faults in dynamic systems can lead to significant consequences, such as performance degradation, safety hazards, or economic losses. Monitoring, detecting, and diagnosing these faults promptly and accurately is essential. Petri Nets provide a graphical and mathematical tool for modelling and analysing dynamic systems but have limitations in handling feedback control loops, nonlinear dynamics, uncertainties, and multiple faults. This thesis addresses these challenges by proposing an integrated Petri Net methodology for fault detection and diagnosis, combining extended Generalised Stochastic Petri Net (xGSPN) for system operation modelling and modified Bayesian Stochastic Petri Net (mBSPN) for fault diagnosis.